VizieR Online Data Catalog: V1241 Tau and GQ Dra light curves (Ulas+, 2020) - Ulas, B.; Gazeas, K.; Liakos, A.; Ulusoy, C.; Stateva, I.; Erkan, N.; Napetova, M.; Iliev, I. Kh. (VizieR Online Data Catalog, 2021)
The observed light curves of V1241 Tau and GQ Dra in BVRI filters are given. Times of minimum light of V1241 Tau and GQ Dra as derived from our observations and TESS light curves are also listed. (2 data files).
Keywords: Photometry: CCD; Stars: variable